Simple Radiography can Rescue from Dilemma - Chowdhury, Naharuma Aive Hyder; Sultana, Sharmin; Shamsuddin, Abul Kalam; Chanda, Prasanta Kumar (Cardiovascular Journal, 2019)
24 year old young lady came to us with a diagnosis of atrial septal defect (ASD) secundum who lost her follow up since her 4 years of age. Later her history, physical findings and investigations change the diagnosis into supracardiac total anomalous pulmonary venous drainage. Typical ‘snowman sign’ in chest x-ray and transthoracic echo helped to review the case. Proper history taking and careful evaluation by investigation is needful for each individual. Cardiovasc. j. 2019; 12(1): 75-78